Simulasi Penghapus Derau Adaptif Pada Sinyal Tutur - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
The adaptive noise canceller (ANC) is an optimum filter that can be applied when proper reference input is available. The advantages of this method are the adaptation capability and the low output distortion. The use of right step size gives high convergence rate. This research modified the classic ANC to give a higher convergence rate and lower output signal distortion. The first hundred iteration applied fixed step size and then followed by changing steps for the next iterations. These modified step sizes were based on SNR estimations. Computer simulations with white noise, showed that the proposed ANC produced signal distortions 10 to 20 dB lower than that with the classic ANC.